The physician experience of patient to provider prejudice (PPtP) - Doerthe A. Andreae; Sameer Massand; Cheryl Dellasega (Frontiers Media S.A., 2024)
BackgroundPatients can demonstrate prejudice and bias toward minoritized physicians in a destructive dynamic identified as PPtP (Patient Prejudice toward Providers). These interactions have a negative impact on the physical and mental well-being of both those who are targeted and those who witness such behaviors.Study purposeThe purpose of this study was to explore the PPtP experiences of attending physicians who identify as a minority based on race, ethnicity, citizenship status, or faith preference.MethodsQualitative methodology was used to collect data using in-depth interviews. 15 attending physicians (8 male, 7 female, aged 33-55 years) who identified as minorities based on ethnicity, citizenship status, or faith practices were interviewed individually. Interviews were conducted using a guide validated in previous studies and content analysis was performed by two trained researchers to identify themes.ResultsFive themes were identified: A Continuum of Offenses, Professional Growth through Adversity, Organizational Issues, Role of Colleagues, and Consequences for Provision of Care. Findings suggest that although attending physicians learned to cope with PPtP, the experience of being treated with bias negatively impacted their well-being and work performance. Attending physicians also felt that white majority medical students sometimes treated them with prejudice but expressed a commitment to protecting vulnerable trainees from PPtP.ConclusionThe experience of PPtP occurs consistently throughout a career in medicine, often beginning in the years of training and persisting into the phase of attending status. This makes it imperative to include strategies that address PPtP in order to successfully recruit and retain minoritized physicians.